Relationship between Culture and Work Ethics: The Islamic Perspective - Attahiru, Mustapha Sidi; Al-Aidaros, Al-Hasan Mohammed Hasan; Yusof, Syarifah Md (International Review of Management and Marketing, 2016)
This study determines Islamic work ethics in the Nigerian context with the aim to provide a proposed model for the country, since most of the existing literature on work ethics is derived from non-Islamic perspectives. There has been a paucity of literature, which provides evidence on how work ethics is to be used in our society. In Nigeria, the Islamic work ethics is traced back during the Islamic sharia period of the Sokoto caliphate. However, immediately after the Nigerian independence, the formation of Nigerian constitutions work ethics on Islamic sharia was terminated, and that gave rise to unethical behaviours in all sectors of the country’s development. Therefore, this study is to provide a model that could be useful for work ethics in the Sokoto state as well as other states of Nigeria. Keywords: Islamic Work ethics, Religion, culture JEL Classifications: C610, C623, I23